2014
DOI: 10.1371/journal.pone.0112075
|View full text |Cite
|
Sign up to set email alerts
|

Altered Fronto-Striatal Fiber Topography and Connectivity in Obsessive-Compulsive Disorder

Abstract: Fronto-striatal circuits are hypothesized to be involved in the pathophysiology of obsessive-compulsive disorder (OCD). Within this circuitry, ventral frontal regions project fibers to the ventral striatum (VS) and dorsal frontal regions to the dorsal striatum. Resting state fMRI research has shown higher functional connectivity between the orbitofrontal cortex (OFC) and the dorsal part of the VS in OCD patients compared to healthy controls (HC). Therefore, we hypothesized that in OCD the OFC predominantly pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…In more than half of individuals with OCD, these symptoms may be severe enough to cause absence from work, school or social engagements; further, treatment of these severe cases is often more difficult (Bourne et al, 2012). Importantly, obsessions and compulsions represent dysfunctional cognitive and motor processes that become repetitive and disturbing; it is suggested that hyperactivation within CSTC circuits and changes to CSTC topography may underlie such ritualistic thoughts and behaviors (Graybiel and Rauch, 2000; Nakamae et al, 2014). …”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%
“…In more than half of individuals with OCD, these symptoms may be severe enough to cause absence from work, school or social engagements; further, treatment of these severe cases is often more difficult (Bourne et al, 2012). Importantly, obsessions and compulsions represent dysfunctional cognitive and motor processes that become repetitive and disturbing; it is suggested that hyperactivation within CSTC circuits and changes to CSTC topography may underlie such ritualistic thoughts and behaviors (Graybiel and Rauch, 2000; Nakamae et al, 2014). …”
Section: Abnormalities Of Sn-cstc Loop Circuits In Psychiatric Illnessesmentioning
confidence: 99%
“…Determining whether striatal hyperactivity originates in striatum or in upstream cortical projections could help inform whether neuromodulatory treatments for OCD-related disorders should target cortical or subcortical regions. Although striatal deep brain stimulation has reported efficacy in OCD (Greenberg et al, 2010;Figee et al, 2013), studies demonstrating aberrant activity in corticostriatal circuits in OCD patients Menzies et al, 2008;Harrison et al, 2009;Del Casale et al, 2011;Figee et al, 2013;Nakamae et al, 2014) suggest that cortical regions may be useful targets for noninvasive neurostimulation via repetitive transcranial magnetic stimulation (rTMS), either through direct cortical effects or modulation of connected subcortical structures. Consistent with this idea, orbitofrontal cortex (OFC) and presupplementary motor area (pre-SMA), which are hyperactive in OCD patients (Maltby et al, 2005;Yücel et al, 2007;Leckman et al, 2010;Del Casale et al, 2011;de Wit et al, 2012;Grützmann et al, 2016), have been identified as promising targets for rTMS (Berlim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Obsessive-compulsive disorder (OCD) is a common psychiatric disorder with a lifetime prevalence of 2-3% 1 that is characterized by obsessions (recurrent intrusive thoughts with excessive anxiety) and compulsions (excessive repetitive actions for reducing obsessioninduced anxiety). Previous neuroimaging studies using structural and task-based functional magnetic resonance imaging (fMRI) have revealed neurobiological dysfunctions in OCD, most notably in the fronto-striatal circuit [2][3][4][5][6] . A meta-analysis of task-based fMRI studies using the symptom provocation paradigm revealed consistent increased activation within fronto-striatal regions 7 .…”
Section: Introductionmentioning
confidence: 99%